The role of HSPA14 in breast cancer: implications for tumorigenesis, immune response modulation, and personalized therapies - Ruipeng Zhao; Xiaocun Zhu; Wan Wei; Linlin Zhen (International Journal of Hyperthermia, 2025)
Background Heat shock proteins have been implicated in the process of carcinogenesis. HSPA14, a member of the heat shock protein family, remains poorly understood in terms of its significance and pathomechanisms in breast cancer.Methods We analyzed the expression levels of HSPA14 and its prognostic significance in breast cancer using TCGA data. TCGA data was used to investigate the association between HSPA14 expression and clinicopathological features in breast cancer patients. GSEA analysis was conducted to identify the biological function of HSPA14. Spearman’s correlation analysis was performed to examine the correlation between HSPA14 expression and immune cell infiltration, as well as immune checkpoint genes. Single cell transcriptomic data from GSE114727 was utilized to calculate the expression of HSPA14 in different cell subpopulations. The data on HSPA14 levels and drug sensitivity were extracted from the CellMiner dataset. The mRNA expression of HSPA14 was validated through cell experiments.Results HSPA14 expression is elevated in breast cancer, which is associated with poor overall survival. It can serve as a diagnostic biomarker for breast cancer patients. Pathway analysis revealed that HSPA14-associated differential genes are involved in cell cycle, apoptosis, cellular response to heat stress, and more. Additionally, HSPA14 expression is significantly correlated with the immune microenvironment. The expression of HSPA14 may also indicate drug sensitivity.Conclusion Our study elucidates the involvement of HSPA14 in tumorigenesis, particularly in modulating the immune response, shaping the immune microenvironment, and contributing to drug resistance, which are pivotal for the development of personalized breast cancer therapies.